Development and Comparison of Various Coated Hard Capsules Suitable for Enteric Administration to Small Patient Cohorts - Nicole Fülöpová; Sylvie Pavloková; Ivan DeBono; David Vetchý; Aleš Franc (MDPI AG, 2022)
Pharmaceutical technology offers several options for protecting substances from acidic environments, such as encapsulation in enteric capsules or dosage form with enteric coating. However, commercial enteric capsules do not always meet limits for pharmacopeial delayed release, and the coating process is generally challenging. Preparing small enteric batches suitable for clinical use is, therefore, an unsolved problem. This experiment offers a simple coating process of DRcapsTM capsules based on hypromellose (HPMC) and gellan gum to achieve small intestine administration. In addition, DRcapsTM capsules were compared to hard gelatin capsules to evaluate the suitability of the coating method. Both capsules were immersed in dispersions of Eudragit® S 100, Acryl-EZE®, and Cellacefate at concentrations of 10.0, 15.0, and 20.0% and dried. Coated capsules were evaluated by electron microscopy, disintegration, and dissolution test with a two-step pH change (from 1.2 to 6.8, then to 7.5) to simulate passage through the digestive tract. DRcapsTM capsules coated with Eudragit® S and Cellacefate achieved acid resistance. While samples coated with Eudragit® S released their contents within 360 min at pH 6.8 (small intestine), regardless of polymer concentration, capsules with 15.0 and 20.0% coatings of Cellacefate released content at pH 7.5 (colon) within 435 and 495 min, respectively.